Navitoclax combined with Alpelisib effectively inhibits Merkel cell carcinoma cell growth in vitro. (December 2020) - Chteinberg, Emil; Wetzels, Suzan; Gerritsen, Wouter; Temmerman, Lieve; van den Oord, Joost; Biessen, Erik; Kurz, Anna Kordelia; Winnepenninckx, Véronique; Zenke, Martin; Speel, Ernst-Jan; Hausen, Axel zur
Background: Merkel cell carcinoma (MCC) is a highly malignant skin cancer. Despite major treatment improvements during the last decade, up to 50% of patients do not respond to therapy or develop recurrent disease. For these patients, alternative treatment options are urgently needed. Here, we assessed the efficacy of the combination of the BCL-2 inhibitor Navitoclax and the PI3K p110α inhibitor Alpelisib in MCC cell lines. Methods: The expression of BCL-2 was assessed by immunohistochemistry in MCC and MCC cell lines. Treatment with Navitoclax and Alpelisib alone and in combination was performed on four MCC cell lines. The decrease of cell viability during treatment was assessed by XTT assay and visualized for the combinations by 3D combinatorial index plotting. The increase of apoptotic cells was determined by cleaved PARP Western blotting and Annexin V staining. Results: Some 94% of MCCs and all three MCPyV-positive cell lines showed BCL-2 expression. Navitoclax monotreatment was shown to be highly effective when treating BCL-2-positive cell lines (IC50 -values ranging from 96.0 to 323.0 nM). The combination of Alpelisib and Navitoclax resulted in even stronger synergistic and prolonged inhibitions of MCC cell viability through apoptosis up to 4 days. Discussion: Our results show that the anti-apoptotic BCL-2 is frequently expressed in MCC and MCC cell lines. Inhibition of BCL-2 by Navitoclax in combination with Alpelisib revealed a strong synergy and prolonged inhibition of MCC cell viability and induction of apoptosis. The combination of Navitoclax and Alpelisib is a novel potential treatment option for MCC patients.